Role of corporate social responsibility, management practices, organizational behavior in social equity with mediating role of women empowerment: A study of the Islamic banking sector of South Punjab - Basheer, Muhammad Farhan; Ul Hameed, Waseem; Al Zarooni, Majid Ibrahim Mohammed Abdullah; Raoof, Rabeeya; Sattar, Javeria (Frontiers in Psychology, 2022)
The objective of this study was to identify the relationship between corporate social responsibility, management practices, and organizational behavior in social equity with the mediating role of women empowerment in the Islamic banking sector of South Punjab. It is a fact that in the Islamic banking sector South Punjab is facing a crisis in the terms of social equity for the employees and customers. This study was based on the quantitative data collected with a five-point Likert scale to identify the relationship between the variables of the framework. The Smart PLS 3 software was used in this study to measure the primary data. The study concluded that there is an important role of corporate social responsibility, management practices, and organizational behavior when it comes to the management of social equity in the Islamic banking sector of South Punjab. The study is significant because it provides theoretical as well as practical implications quite useful for the Islamic banking sector of South Punjab to cope with the problem of social equity.